Republic of Poland : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2018)
This Technical Assistance Report discusses the findings and recommendations made by the IMF mission about building forward estimates and standardizing the chart of accounts in Poland. The workshops identified a range of cross-cutting issues, with recommendations provided for how to apply them more broadly over the next two years, with ongoing short-term expert support. It is recommended to apply a consistent approach to treating demand driven entitlement programs, by using the existing detailed projection models and methodologies that lie within agencies and funds, but ensuring that all indices and volume parameters are in line with central macroeconomic assumptions to ensure consistency.